Eksplorasi Ambiguitas Konflik pada Pelaksanaan Pendaftaran Tanah Sistematis Lengkap (PTSL) di Desa Maron Kabupaten Kediri - Putri Arum Pertiwi; Gading Gamaputra (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
This study examines the implementation of the Complete Systematic Land Registration program in Maron Village, Kediri Regency, using four criteria for resolving land-related conflicts. PTSL is an initiative launched by the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN) as a manifestation of the government’s commitment to providing legal certainty and protection to the community regarding their land. The objective of this study is to analyze the implementation of the PTSL program in Maron Village, Kediri Regency, based on four dimensions of land accuracy. This study employs a descriptive qualitative method to delve deeper into the implementation of the Complete Systematic Land Registration in Maron Village. Data collection techniques include interviews, observations, and documentation. The results of this study indicate that the implementation of the Complete Systematic Land Registration program in Maron Village faces several challenges. This program was analyzed based on the four dimensions of accuracy proposed by Richard Matland, namely policy accuracy, implementation accuracy, target accuracy, and environmental accuracy. Regarding the target accuracy indicator, the program did not meet its objectives because of the community’s limited knowledge regarding legal data and other constraints, which resulted in some community members not participating in the program.